USE OF THE THERAPEUTIC ULTRASOUND AND LASER THERAPY IN THE INITIAL FORMATION OF BONE CALLUS ABSTRACT (Fiep Bulletin - online, 2013)
The present study the application of irradiation with laser in the initial formation of osseous callus in association to spica cast had as objective to verify the effect of the application of the UST (therapeutical ultrasound) of comparative. The study it used of eighteen rats, with average corporal weight of 380g. All the procedures had been carried through in compliance with the norms and ethical principles in research with animals and approved by CEP - UNIARAXÁ. The animals had been divided in three experimental groups (A, B and C) composites for six animals each. The animals had been submitted to the experimental production of the fracturing in the right tibia, produced to the level of the 1/3 tibial distal, through manual pressure, being that after the production of the fractures all the groups had been immobilized with spica cast device. In the group associate to the stimulation with UST was carried through it IG (1MHz, pulsed: 50%, intensity: 0,5 W/cm2); in group B the animals had been submitted IG and applied the laser pontual in 4 J/cm2, and group C it served only of control of the study, being only submitted to the protocol of spica cast immobilization. For the analysis of initial formation of osseous callus, after the period of treatment, the animals f all the groups had been day sacrificed and carried through radiographic examinations in the posterior-previous incidence in 15º day. In the radiographic analysis of the group dealt with laser, the beginning of formation of osseous callus was greater that the too much groups. We suggest through the joined results that the UST sped up the osseous repair, however, the laser was capable to speed up with bigger potentiality the initial formation of osseous callus in relation to the other analyzed groups.
Keywords: fractures; ultrasound; laser